Modern Radiation Therapy for the Management of Brain Metastases From Non-Small Cell Lung Cancer: Current Approaches and Future Directions - Mantovani, Cristina; Gastino, Alessio; Cerrato, Marzia; Badellino, Serena; Ricardi, Umberto; Levis, Mario (Frontiers in Oncology, 2021)
Brain metastases (BMs) represent the most frequent event during the course of Non-Small Cell Lung Cancer (NSCLC) disease. Recent advancements in the diagnostic and therapeutic procedures result in increased incidence and earlier diagnosis of BMs, with an emerging need to optimize the prognosis of these patients through the adoption of tailored treatment solutions. Nowadays a personalized and multidisciplinary approach should rely on several clinical and molecular factors like patient’s performance status, extent and location of brain involvement, extracranial disease control and the presence of any “druggable” molecular target. Radiation therapy (RT), in all its focal (radiosurgery and fractionated stereotactic radiotherapy) or extended (whole brain radiotherapy) declinations, is a cornerstone of BMs management, either alone or combined with surgery and systemic therapies. Our review aims to provide an overview of the many modern RT solutions available for the treatment of BMs from NSCLC in the different clinical scenarios (single lesion, oligo and poly-metastasis, leptomeningeal carcinomatosis). This includes a detailed review of the current standard of care in each setting, with a presentation of the literature data and of the possible technical solutions to offer a “state-of-art” treatment to these patients. In addition to the validated treatment options, we will also discuss the future perspectives on emerging RT technical strategies (e.g., hippocampal avoidance whole brain RT, simultaneous integrated boost, radiosurgery for multiple lesions), and present the innovative and promising findings regarding the combination of novel targeted agents such as tyrosine kinase inhibitors and immune checkpoint inhibitors with brain irradiation.